Salazar Slytherin as a Gothic Archetype: A Baldickian Interpretation of the Tyranny of the Past - Md. Alamin Sarker (English Education Program, Education Faculty, Universitas Nurul Huda, 2026)
This paper aims to provide a detailed literary analysis of Salazar Slytherin, a character from J. K. Rowling’s Harry Potter book series (1997–2007), as a quintessential Gothic figure. It repositions the 10th-century founder of Hogwarts not just as a historical enemy in the Wizarding World, but as a key figure in the Gothic tradition. The study focuses on the ideas of critic Chris Baldick, who identifies several aspects of Gothic literature, such as the